2011
DOI: 10.1016/j.apunts.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Hemofilia: ejercicio y deporte

Abstract: Resumen El ejercicio físico y el deporte constituyen uno de los pilares básicos en el tratamiento de la hemofilia. Este trabajo describe un resumen de las características de la hemofilia y, a través de una exhaustiva revisión bibliográfica, se analiza la importancia de la condición física, en relación con la prevención y el tratamiento de las lesiones musculoesqueléticas en el paciente hemofílico.La hemofilia es una enfermedad hematológica hereditaria, con lesiones ortopédicas características. Afecta a individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 81 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…Querol et al [1] in a study about exercise and sports have observed that physicians usually recommend limited physical activity in children with haemophilia. There are few studies indicate that physical activity in children with haemophilia is adequate.…”
mentioning
confidence: 99%
“…Querol et al [1] in a study about exercise and sports have observed that physicians usually recommend limited physical activity in children with haemophilia. There are few studies indicate that physical activity in children with haemophilia is adequate.…”
mentioning
confidence: 99%